2013
DOI: 10.1111/2041-210x.12127
|View full text |Cite
|
Sign up to set email alerts
|

Estimating multispecies abundance using automated detection systems: ice‐associated seals in the Bering Sea

Abstract: Summary1. Automated detection systems employing advanced technology (e.g. infrared imagery, auditory recording systems, pattern recognition software) are compelling tools for gathering animal abundance and distribution data since investigators can often collect data more efficiently and reduce animal disturbance relative to surveys using human observers. 2. Even with these improvements, analysing animal abundance with advanced technology can be challenging because of potential for incomplete detection, false p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
118
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(125 citation statements)
references
References 36 publications
2
118
0
5
Order By: Relevance
“…In some cases, it may be possible to reduce commission error rates to the point where manual review of automated analysis results is not necessary, while in other cases, like ours, varying degrees of manual postanalysis effort may be required. Although animal contrast in thermal-infrared imagery has proven useful for automated detection of mammals (Conn et al 2014, Chrétien et al 2015, 2016, Seymour et al 2017, the very coarse pixel resolution of thermal cameras compared to RGB cameras generally renders them ineffective for aerial detection of comparatively smaller birds (Chabot and Francis 2016). It should be noted that any aerial image-based survey will only allow detection of subjects that are visible from overhead and miss subjects that are, for example, concealed under canopy or diving underwater.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, it may be possible to reduce commission error rates to the point where manual review of automated analysis results is not necessary, while in other cases, like ours, varying degrees of manual postanalysis effort may be required. Although animal contrast in thermal-infrared imagery has proven useful for automated detection of mammals (Conn et al 2014, Chrétien et al 2015, 2016, Seymour et al 2017, the very coarse pixel resolution of thermal cameras compared to RGB cameras generally renders them ineffective for aerial detection of comparatively smaller birds (Chabot and Francis 2016). It should be noted that any aerial image-based survey will only allow detection of subjects that are visible from overhead and miss subjects that are, for example, concealed under canopy or diving underwater.…”
Section: Discussionmentioning
confidence: 99%
“…Airborne UVA/VIS/NIR/SWIR camera systems could also be used. One option would be to use moderate resolution multi-spectral imagery (e.g., 0.5-1.0 m pixels) to detect potential bears based on the spectral signature, combined with higher resolution (e.g., 0.1 m) standard photographs to verify species identification visually, using techniques analogous to those of [13].…”
Section: Discussionmentioning
confidence: 99%
“…Polar bear fur is highly absorbent in the lower ultraviolet (UVA) region, in contrast to snow, and as such, when imaged in the UVA range, polar bears appear black against a white snow background [19,20,22]. Thermal infrared (TIR) (3000-12,000 nm) imaging has been used to survey a variety of arctic mammals, including walrus [23] and seals (e.g., [13]), and could potentially detect polar bears [21]. Early attempts to detect polar bears with thermal imaging met with limited success [24], but this was likely due to the limited sensitivity of the equipment used, given that subsequent studies have shown that exercising bears radiate heat several degrees warmer than the ambient temperatures [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that more hauled-out seals may have been encountered had the aerial surveys been conducted mid-day as recommended by Lake et al (1997), and if more frequent surveys were conducted within and between seasons. We, therefore, recommend that future surveys in the area take into account the time of the aerial surveys and adopt standardized, quantitative methods for design or model-based estimates such as those used by Southwell (2005), Conn et al (2013), andver Hoef et al (2014).…”
Section: Discussionmentioning
confidence: 99%